Hiatal hernia after esophagectomy – a report of two cases - Maciąg, Bogumił; Wójcik, Janusz; Pieróg, Jarosław; Wójcik, Norbert; Witkiewicz, Karina; Grodzki, Tomasz (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2017)
Postoperative hiatal hernia after esophagectomy occurs with a frequency of 0.4–6%, and the local conditions following esophagectomy promote its occurrence. In the material presented here, hiatal hernia in the form of displacement of the colon to the mediastinum was established in 0.78% (2/256) of all performed esophagectomies. Both cases were reoperated successfully.